Remanent magnetization of maghemitized basalts from Krafla drill cores, NE-Iceland (Dataset) ... - Oliva-Urcia, Belén; Kontny, Agnes (Magnetics Information Consortium (MagIC), 2023)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Remanent magnetization of maghemitized basalts from Krafla drill cores, NE-Iceland ...